Diagnosis of moral competence and gender difference of university students - Robles Francia, Víctor Hugo; de la Cruz-Caballero, Adriana Mariela; Robles-Ramos , Víctor Adrián; Banda-Guzmán, Judith (Acta Universitaria, 2022)
Moral competence is fundamental in university students, therefore, its effective measurement, based on the moral emotions that drive moral behavior, is essential. The objective of this research was to carry out the evaluation of moral competence in students of the University of Guanajuato in Mexico and to compare the level of this competence between women and men. The moral emotional test (MET), designed using moral emotions, was applied to a sample of 270 participants, 167 women and103 men. The results showed a population value of moral competence of 32.85, and the Mann-Whitney U test produced significance values higher than 0.05 in gender. It is concluded that the level of moral competence of the participants obtained a medium value, and that men and women equally develop cognitive and emotional skills to act in the right way.